2021
DOI: 10.1002/cctc.202002039
|View full text |Cite
|
Sign up to set email alerts
|

A Durable Metalloporphyrin 2D‐Polymer for Photocatalytic Hydrogen and Oxygen Evolution from River and Sea Waters

Abstract: It is highly imaginary that the outcome of a combination of two complementary resources leads to answer an alarming global issue. One such possible example is the solar seawater splitting for ‘clean fuel’ H2 generation. Since the catalytic activity and stability of the photocatalysts are substantially challenged in seawater, the design of an efficient and stable photocatalyst is highly desirable. Herein, we demonstrate the solar seawater splitting by a two‐dimensional polymer catalyst derived from metalloporph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…This material was further developed by the same research team in the following years. 118 The authors used different metal ions to metallate the porphyrin 2D-polymer, namely Co( ii ), Ni( ii ) and Zn( ii ), and synthesized the four derivatives described in Fig. 19d.…”
Section: Porphyrins For Photocatalytic H2 Productionmentioning
confidence: 99%
“…This material was further developed by the same research team in the following years. 118 The authors used different metal ions to metallate the porphyrin 2D-polymer, namely Co( ii ), Ni( ii ) and Zn( ii ), and synthesized the four derivatives described in Fig. 19d.…”
Section: Porphyrins For Photocatalytic H2 Productionmentioning
confidence: 99%
“…This study makes using two-dimensional polymers as a bifunctional catalyst for sunlight-induced water splitting more evident. 108 Lu et al (2022) reported that carbon nitride tubes that are hollow and lled with carbon dots have been used for producing hydrogen from water or saltwater with the help of light.…”
Section: Carbon Based Catalystsmentioning
confidence: 99%
“…This study makes using two-dimensional polymers as a bifunctional catalyst for sunlight-induced water splitting more evident. 108…”
Section: Photocatalytic Natural Seawater and Artificial Seawater Spli...mentioning
confidence: 99%
“…Facile preparation, functionality, modularity, stability, and scalability have made these frameworks ideal for different applications. [16][17][18] The intrinsic porosity and high crystallinity of COFs make them suitable for gas [19][20][21][22][23][24][25] and energy storage, [26][27][28][29][30][31][32][33][34] targeted drug delivery, [35][36][37][38][39] molecular sorption and separation, [40][41][42][43][44][45] molecular sensing, [46][47][48][49][50] catalysis [51][52][53][54][55][56][57][58] etc. Though different applications have been explored for COF, the synthetic methodologies adopted limited the bulk-scale synthesis of these materials.…”
Section: Introductionmentioning
confidence: 99%